The impact of global surrounding on the common agricultural policy - Wieliczko, Barbara (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The global factors have been influencing the shape of the common agricultural policy (CAP) at least since the WTO agreement. Yet, not only trade agreements influence the CAP. The situation of agricultural sector in non-EU countries also affects the way and extent the EU supports its farmers. Moreover, the EU interests in other sectors of economy or its global strategy and policy interests can translate into specific alterations in the CAP. The aim of the paper is to identify the meeting points between CAP and global issues, present the status quo and analyze potential alterations within the CAP that could be made to strengthen the EU position on the world arena. The paper is based on the analyses of the WTO negotiations concerning agriculture, CAP policy instruments and the EU priorities in external relations. The results show that the process of CAP’s internationalization progresses in a non-linear way but is an important factor determining the shape of subsequent CAP reforms
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 498, s. 374-381
Keywords: common agricultural policy; global agri-food trade; policy instruments; wspólna polityka rolna; globalny handel produktami rolno-spożywczymi; instrumenty polityki